How do policy evaluators understand complexity?. (July 2020) - Barbrook-Johnson, Pete; Proctor, Amy; Giorgi, Sara; Phillipson, Jeremy
There is a well-documented interest in how insights from the study of complexity can be applied to policy evaluation. However, important questions remain as to how complexity is understood and used by policy evaluators. We present findings from semi-structured interviews with 30 UK policy evaluators working in food, energy, water and environment policy domains. We explore how they understand, use and approach complexity, and consider the implications for evaluation research and practice. Findings reveal understandings of complexity arising from contextual factors, scale-related issues and perceptions of unpredictability. The evidence indicates terminological and analogical use of complexity and its concepts by policy evaluators, but limited evidence of its literal use. Priorities for the future include framing complexity more pragmatically and as an opportunity not a cost. Communicating this up the policy hierarchy is the key to progressing complexity-appropriate evaluation – this can be enabled by strengthening links between policy evaluation and academic communities.